AN ANALYSIS OF THE LESSON PLANS CONSTRUCTED BY STUDENTS IN MICRO TEACHING CLASS BASED ON ASPECTS OF ASSESSMENT A LESSON PLAN - Lalia, Istiq; Ariyani, Amra; Radhiyani, Fitri (State University of Makassar, 2024)
This study aims to clarify and show the results of the assessment from lesson plans constructed by students in micro teaching classes. It was a descriptive quantitative research. The study was carried out at Universitas Negeri Makassar in the area of English language education. The data was obtained from Universitas Negeri Makassar's fifth semester English Language Education students. In class D, the researcher took as a sample twenty-six lesson plans from fifth semester academic year 2021-2022. Document analysis was an instrument of the research. The student data that has been collected is being combined and analyzed. Five aspects of assessment lesson plans were used to determine students' scores. The researcher then assigned four categories of scores from the lesson plan to be classified; very good, good, fair, and poor. Based on the result of the students’ in constructing lesson plans from all aspects of assessment, that the students from fifth semester at English Language Education of Universitas Negeri Makassar were almost ranged in the